Abstracts 2019
DOI: 10.1136/lupus-2019-lsm.238
|View full text |Cite
|
Sign up to set email alerts
|

238 Leukocyte immunoglobulin-like receptor A3 (LILRA3) promotes lupus-like disease in a murine lupus model

Abstract: BackgroundLeukocyte immunoglobulin-like receptor A3 (LILRA3) is a secreted protein belongs to LILR family. Our research group previously reported that the functional LILRA3 is a novel genetic risk for multiple autoimmune diseases including systemic lupus erythematosus (SLE). However, the function of LILRA3 in development of lupus is unclear. The bm12 model is a chronic graft-versus-host disease (cGVHD) model characterized by the lupus-like syndrome with cell subtype alteration and autoantibody production. To f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…A recent study reported that LILRA3 amount in both serum and CD14 + monocytes were significantly elevated and positively correlated with disease severity in SLE patients (132). Data from humanized mice suggest LILRA3 as a promoter of excessive expression of T follicular helper cells and B cells, which primes the induction and maintenance of plasma cell differentiation and autoantibody production (133). Of note, enhanced expression of LILRB1 was achieved after ex vivo IL-10 stimulation of DCs isolated from SLE patients (134).…”
Section: Beyond Infections: Lilrs In Inflammation and Autoimmunitymentioning
confidence: 99%
“…A recent study reported that LILRA3 amount in both serum and CD14 + monocytes were significantly elevated and positively correlated with disease severity in SLE patients (132). Data from humanized mice suggest LILRA3 as a promoter of excessive expression of T follicular helper cells and B cells, which primes the induction and maintenance of plasma cell differentiation and autoantibody production (133). Of note, enhanced expression of LILRB1 was achieved after ex vivo IL-10 stimulation of DCs isolated from SLE patients (134).…”
Section: Beyond Infections: Lilrs In Inflammation and Autoimmunitymentioning
confidence: 99%